Diagnostic application and clinical significance of FCM progress scoring system based on immunophenotyping in CD34+ blasts in myelodysplastic syndromes. Issue 4 (29th March 2013) - Xu, Feng; Guo, Juan; Wu, Ling‐Yun; He, Qi; Zhang, Zheng; Chang, Chun‐Kang; Li, Xiao
<x xml:space="preserve">Abstract</x> Background Abnormal proliferation and differentiation of hematopoietic stem/progenitor cells, which reflect the malignant nature of clonal cells in myelodysplastic syndromes (MDS), can be detected by flow cytometry (FCM) and potentially applied to assist diagnosis and evaluate prognosis in MDS. Methods In this study, a series of immunophenotypes such as CD34, CD19, CD38, CD117, and CD7, which are related to proliferation and differentiation of HSCs, were determined by FCM in the patients with nonclonal cytopenias diseases and MDS. Based on the expression pattern of these immunophenotypes, a FCM progress scoring (FPS) system was constructed and evaluated. Results The FPS system showed good sensitivity and specificity (63.6% and 100.0%) in distinguishing MDS from nonclonal cytopenias diseases. Validation analysis of FPS system indicated comparable sensitivity and specificity (73.7% and 97.1%) and high agreement rate (82.6%) of FCM diagnosis with morphological diagnosis. The high‐grade MDS had higher FPS score compared to low‐grade MDS (P < 0.001). Noticeably, hypocellular MDS had lower FPS score (P < 0.001), most of which could not be diagnosed by FPS system. Besides, FPS score showed obvious positive correlation with WHO classification, IPSS score, percentage of marrow blasts, and cytogenetic prognosis scoring. Elevated FPS score predicted higher disease progression and shorter survival in MDS. Conclusion The FPS system based on immunophenotyping in CD34+ blasts is a useful and simple tool for diagnosis and prognosis evaluation in MDS. © 2013 International Clinical Cytometry Society